AlF3-modified LiCoPO4 for an advanced cathode towards high energy lithium-ion battery. Issue 2 (1st February 2018) - Wang, Yue; Qiu, Jingyi; Yu, Zhongbao; Ming, Hai; Li, Meng; Zhang, Songtong; Yang, Yusheng
Abstract: Surface-interface reaction between the electrode and electrolyte plays a key role in lithium-ion storage properties, especially for high voltage cathode such as LiCoPO4 and Ni-riched cathode. Generally, surface modification is an effective method to improve the electrochemical performance of electrode materials. Herein, in order to revise the LiCoPO4 cathode with desirable properties, uniform AlF3 -modified LiCoPO4 (LiCoPO4 @AlF3 ) cathode materials in nano-sized distribution are synthesized. XRD result indicates that there is no structural transformation observed after AlF3 coating. TEM characterization and XPS analysis reveal that the surface of LiCoPO4 particle is coated by a nano-sized uniform AlF3 layer. Further, the electrochemical results indicate that AlF3 layer significantly improves the cycling and rate performances of LiCoPO4 cathode within the voltage range of 3.0–5.0 V. After a series of optimization, 4 mol% AlF3 -coated LiCoPO4 material exhibits the best properties including an initial discharge capacity of 159 mA h g −1 at 0.1 C with 91% capacity retention after 50 cycles, especially a discharge capacity of 90 mA h g −1 can be obtained at 1 C rate. CV curves indicate that the polarization of cathode is reduced by AlF3 layer and EIS curves reveal that AlF3 layer relieves the increase of resistance to facilitate Li-ion transfer at the interface between electrode and electrolyte during the cycling process. The enhanced electrochemical performances are attributed to that the AlF3 layer can stabilize the interface between the cathode and electrolyte, form steady SEI film and suppress the electrolyte continuous decomposition at 5 V high voltages. This feasible strategy and novel characteristics of LiCoPO4 @AlF3 could promise the prospective applications in the stat-art of special lithium-ion battery with high energy and/or power density.